Biomes : discover the Earth's ecosystems with environmental science activities for kids - Latham, Donna ("Build it yourself" series., 2019)
Explores the history and science of Earth's nine terrestrial and aquatic biomes. Includes text-related activities and experiments, a glossary, and color photographs.